Letter from William J. Mac Brien proposing repayment schedule to Cumann na bPíobairí, - Mac Brian, Wiliam J. (1907)
Letter from William [Liam] J. Mac Brien at St. Stephen's House, Cannon Row, Whitehall, London. Referring to a letter from Mr. Lavelle [P. Lavelle, solicitor] asking him to forward money and papers to Cumann na bPíobairí, he asks for more time to clear his debt, citing his recent move from Dublin, other debts and ill health. He guarantees to return the papers by the following Monday and proposes a repayment schedule. He states "If you cannot see your way to be so far merciful I can only wait for you to put the law in motion as I have no money other than my monthly pay".